24
60
594
8,142
705,186
21,426,678
Answer:
it would contain a Euler path
Step-by-step explanation:
![\displaystyle\\Answer:\ y=\sqrt{\frac{x-1}{2} } \ \ \ \ (x\geq 1,\ \ \ \ y\geq 0)](https://tex.z-dn.net/?f=%5Cdisplaystyle%5C%5CAnswer%3A%5C%20y%3D%5Csqrt%7B%5Cfrac%7Bx-1%7D%7B2%7D%20%7D%20%20%5C%20%5C%20%5C%20%5C%20%28x%5Cgeq%201%2C%5C%20%5C%20%5C%20%5C%20y%5Cgeq%200%29)
Step-by-step explanation:
![y=2x^2+1\\](https://tex.z-dn.net/?f=y%3D2x%5E2%2B1%5C%5C)
<em>We change the argument and the value:</em>
![\displaystyle\\x=2y^2+1\\\\x-1=2y^2+1-1\\\\x-1=2y^2\\](https://tex.z-dn.net/?f=%5Cdisplaystyle%5C%5Cx%3D2y%5E2%2B1%5C%5C%5C%5Cx-1%3D2y%5E2%2B1-1%5C%5C%5C%5Cx-1%3D2y%5E2%5C%5C)
<em>Divide both parts of the equation by 2:</em>
![\displaystyle\\\frac{x-1}{2}=y^2\\\\ \sqrt{\frac{x-1}{2} }=y \ -\ the\ desired\ inverse\ function\\\\](https://tex.z-dn.net/?f=%5Cdisplaystyle%5C%5C%5Cfrac%7Bx-1%7D%7B2%7D%3Dy%5E2%5C%5C%5C%5C%20%5Csqrt%7B%5Cfrac%7Bx-1%7D%7B2%7D%20%7D%3Dy%20%5C%20%20-%5C%20%20the%5C%20%20desired%5C%20%20inverse%5C%20%20function%5C%5C%5C%5C)
<em>The restrictions are imposed on the inverse function by on x:</em>
![x-1\geq 0\\x\geq 1](https://tex.z-dn.net/?f=x-1%5Cgeq%200%5C%5Cx%5Cgeq%201)
<em>The restrictions are imposed on the inverse function by on y:</em>
![y\geq 0](https://tex.z-dn.net/?f=y%5Cgeq%200)
<em>Then the original function is defined on the sets:</em>
![x\geq 1,\ \ \ \ y\geq 0](https://tex.z-dn.net/?f=x%5Cgeq%201%2C%5C%20%5C%20%5C%20%5C%20y%5Cgeq%200)
<em>The initial function, a parabola, is constrained because of the inverse function; only in this case the functions are reciprocal.</em>
Answer:
For every hour the car is parked, the cost increases by $5.
Step-by-step explanation:
The cost, in dollars, of parking a car in a busy downtown area for h hours is $15 + $5h.
The fixed cost for the parking is $15. Here, $5 is extra. It increases as the number of hours increases. For every hour, the cost increases by $5. Hence, the correct statement for the given problem is (C) "for every hour the car is parked, the cost increases by $5".
Answer:
x= -15 or (7x+5)
Step-by-step explanation:
Simplifying
4x + 10 = 3x + -5
Reorder the terms:
10 + 4x = 3x + -5
Reorder the terms:
10 + 4x = -5 + 3x
Solving
10 + 4x = -5 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
10 + 4x + -3x = -5 + 3x + -3x
Combine like terms: 4x + -3x = 1x
10 + 1x = -5 + 3x + -3x
Combine like terms: 3x + -3x = 0
10 + 1x = -5 + 0
10 + 1x = -5
Add '-10' to each side of the equation.
10 + -10 + 1x = -5 + -10
Combine like terms: 10 + -10 = 0
0 + 1x = -5 + -10
1x = -5 + -10
Combine like terms: -5 + -10 = -15
1x = -15
Divide each side by '1'.
x = -15
Simplifying
x = -15